2021
DOI: 10.1099/jmm.0.001410
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection to control African swine fever virus: a UK perspective

Abstract: A review of African swine fever (ASF) was conducted, including manifestations of disease, its transmission and environmental persistence of ASF virus. Findings on infectious doses of contemporary highly-pathogenic strains isolated from outbreaks in Eastern Europe were included. Published data on disinfectant susceptibility of ASF virus were then compared with similar findings for selected other infectious agents, principally those used in the UK disinfectant approvals tests relating to relevant Disease Orders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
(137 reference statements)
1
8
0
Order By: Relevance
“…Another typical example is given by Shirai et al for the didecyldimethyl ammonium cation [34]. Indeed, DDAC was very effective against the African swine fever virus (enveloped), but it was less effective against swine vesicular disease virus (non-enveloped), even to a tenfold higher working concentration than one used with the enveloped virus [35]. Electron microscopic observation revealed that the cationic surfactant induced disruption of the lipid outer membrane of the enveloped viruses as previously mentioned.…”
Section: Comparison With Other Disinfection Systemsmentioning
confidence: 75%
“…Another typical example is given by Shirai et al for the didecyldimethyl ammonium cation [34]. Indeed, DDAC was very effective against the African swine fever virus (enveloped), but it was less effective against swine vesicular disease virus (non-enveloped), even to a tenfold higher working concentration than one used with the enveloped virus [35]. Electron microscopic observation revealed that the cationic surfactant induced disruption of the lipid outer membrane of the enveloped viruses as previously mentioned.…”
Section: Comparison With Other Disinfection Systemsmentioning
confidence: 75%
“…The obtained result became possible thanks to the use of a two-component disinfectant based on glutaraldehyde [31] and didecyl dimethyl ammonium chloride in a concentration of 3 %, which made it possible to inhibit the process of biological corrosion of concrete and strengthen the concrete structure. Strengthening of concrete occurs through the use of a component of the disinfectant -glutaraldehyde, which has the ability to fix organic and inorganic substances [32]. In addition, glutaraldehyde in the composition of other biocides was tested to protect building structures from damage by microscopic fungi [33].…”
Section: Discussion Of Results Of Studying the Biochemical Corrosion ...mentioning
confidence: 99%
“…The risk of the ASF virus entering the UK through imported pig products is currently assessed as medium. Dr Andy Wales from the University of Surrey gave an update on the challenge of disinfecting after an outbreak of ASF, based on a detailed review of the literature [21]. Data on disinfection of ASF virus (ASFV) was compared to data available for disinfection of Salmonella , the organism used for the Defra general orders disinfectant testing.…”
Section: Overviewmentioning
confidence: 99%
“…The variability of available data was highlighted, for example studies often vary in the level of organic matter used, the concentration of disinfectant, test temperature, water hardness and test environment, suspension or surface. In conclusion, with limited data available, chlorine-based disinfectants had the strongest evidence of efficacy against ASFV when used at general orders concentration and there was also reasonable evidence for glutaraldehyde-based disinfectants and for some acidic peroxygen class disinfectants, when also used at general orders concentration [21]. An additional benefit of using the general orders concentration is that this can provide more successful disinfection against other exotic livestock viruses, such as swine vesicular disease virus and foot-and-mouth disease virus [21], under challenging conditions and is also more likely to be effective against additional unidentified bacterial pathogens on farms affected by notifiable disease.…”
Section: Overviewmentioning
confidence: 99%